2022
DOI: 10.1155/2022/2480746
|View full text |Cite
|
Sign up to set email alerts
|

Digital Evaluation of Nitrite-Reduced “Kulen” Fermented Sausage Quality

Abstract: This study aimed to evaluate nitrite reduction impact on geometry, colour, chemical, microbiological, and sensory traits of dry sausage (kulen) traditionally prepared with red hot paprika powder. Three batches of kulen with different nitrite levels were produced and assessed: N110 (control with 110 mg/kg of sodium nitrite), N55 (55 mg/kg of sodium nitrite), and NF (without sodium nitrite). Samples for the analyses were taken on production day, after 8, 16, 24, 32, and 40 days of ripening and after 50 and 100 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The relative error of 3D volume measurements ranged from 1.9 % to 4.5 %, depending on the processing stage. These values are similar to those found by Zhang et al (2019) and Simunovic et al (2022), but higher than those reported by Goni et al (2007). Generally, there are four main groups of characteristics that have been analyzed in fermented sausages: physico-chemical, textural, sensory and microbiological.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The relative error of 3D volume measurements ranged from 1.9 % to 4.5 %, depending on the processing stage. These values are similar to those found by Zhang et al (2019) and Simunovic et al (2022), but higher than those reported by Goni et al (2007). Generally, there are four main groups of characteristics that have been analyzed in fermented sausages: physico-chemical, textural, sensory and microbiological.…”
Section: Resultssupporting
confidence: 87%
“…The duration of one scan was approximately 40 min. Meshing of 3D scans was performed using EXScan S_v3.0.0.1 (Shining 3D Tech., Hangzhou, China) software as described by Simunovic et al (2022). Relative error (%) of 3D estimated volume was measured during each stage using the water displacement method.…”
Section: D Laser Imagingmentioning
confidence: 99%
“…In a recent study, Simunovic et al (2022a) produced traditionally fermented kulen sausage with 50% nitrite reduction and without nitrite. The goal of the study was to evaluate the influence of sodium nitrite on various quality parameters of the product.…”
Section: Nitrite Reductionmentioning
confidence: 99%
“…Levels of free fatty acids were the highest in sausages formulated without nitrites, but similar between sausages formulated with 110 mg/kg or 55 mg/kg of sodium nitrite, which is in accordance with the levels of TBARS. The study of Simunovic et al (2022a) revealed that oral processing parameters differed, depending on the level of nitrite. More precisely, the consumption time for one bite(s) and the number of chewing strokes were significantly lower in sausages formulated without nitrites.…”
Section: Nitrite Reductionmentioning
confidence: 99%
See 1 more Smart Citation